Az idő és a távolság szubjektív megítélésének vizsgálata a Hódmezővásárhely környéki tanyavilágban és tanyaközpontokban - Gálné Horváth, Ildikó (Jelenkori Társadalmi és Gazdasági Folyamatok, 2014)
The homesteads and farm centers peculiarly adapted to the socio-economic and geographical space, as well as accordingly residents participate in daily life. Spatial and temporal distance from the town and the socio-economic aspects are of the different farm people. The distance to the town's social impact on the lives, livelihoods of the farm population, this is subjective according to people's point of view. The study assessed many components, of which two daily routine, mail receiving and shipping, and the purchase will be presented.